Solvent‐assisted planar structure of a stilbene‐based salicylhydrazone compound: crystal structure, solvent‐ and aggregation‐induced emission, and switchable luminescence colouration. Issue 8 (6th July 2020) - Fang, Zong-Bin; Zhang, Bin; Yang, Qi-Zheng; Zheng, Wenxu; Hu, Xiao-Lin; Huang, Xi-He; Huang, Chang-Cang; Zhuang, Nai-Feng; Wu, Shu-Ting
Abstract : In the crystal structure of a novel stilbene salicylhydrazone derivative, there is a one‐dimensional channel for DMSO molecules, which may induce the easy removal of DMSO upon heating, and the crystal shows switchable luminescence colouration by simply removing or re‐adding DMSO. Abstract : A novel stilbene‐based salicylhydrazone compound {systematic name: ( E )‐4, 4′‐(ethene‐1, 2‐diyl)bis[( N ′ E )‐ N ′‐(2‐hydroxybenzylidene)benzohydrazide] dimethyl sulfoxide disolvate, C30 H24 N4 O4 ·2C2 H6 OS or L ·2DMSO} was synthesized and characterized by single‐crystal X‐ray diffraction, powder X‐ray diffraction and luminescence spectroscopy. The title compound crystallizes in the monoclinic space group P 21 / c, with half a symmetry‐independent L molecule and one dimethyl sulfoxide (DMSO) solvent molecule in the asymmetric unit. The L molecule adopts an almost planar structure, with a small dihedral angle between the planes of the stilbene and salicylhydrazone groups. There are multiple π–π stacking interactions between adjacent L molecules. The DMSO solvent molecules act as proton donors and acceptors, forming hydrogen bonds of various strengths with the L molecules. In addition, the geometry optimization of a single molecule of L and its luminescence properties either in solution, as a solvated solid or as a desolvated solid were studied. The compound shows an aggregation‐induced emission (AIE) effect and exhibits switchable luminescence colouration in the solid state by the simple removal or re‐addition of the DMSO solvent.